PENGARUH WAKTU PENYINARAN DAN KONSENTRASI AWAL LARUTAN KROMIUM(VI) TERHADAP HASIL FOTOREDUKSI KROMIUM(VI) YANG TERKATALISIS OLEH SEMIKONDUKTOR ZNO-ZEOLIT: EFFECT OF EXPOSURE TIME AND INITIAL CONCENTRATION CHROMIUM(VI) SOLUTION ON PHOTOREDUCTION RESULTS SEMICONDUCTOR CATALYZED Chromium(VI). ZNO-ZEOLITE Buka di Google Terjemahan • Masukan Google Terjemahan - Agnes Dyah Novitasari Lestari (JISTECH: Journal of Information Science and Technology, 2015)
The Yield of a photoreduction process of chromium(VI) or Cr (VI) catalyzed by ZnO semiconductorstructured in the zeolite/ZnO-zeolite (ZnO-Z) can be influenced by several factors, including the exposure timeand the initial concentration of the Cr (VI) solution. In this study, the photoreduction process of Cr (VI) iscarried out in a closed batch reactor equipped with a magnetic stirrer and a 38 Watt UV lamp. A total of 50 mLof a Cr(VI) solution and 25 mg of ZnO-Z was used to study the effect of exposure time and the initialconcentration of the Cr(VI)solution to the yield of its photoreduction process. The concentrations of Cr (VI) weredetermined by UV-Vis spectrophotometer using difenilkarbazid method. To determine the catalyst performanceof ZnO-Z in the photoreduction process, an examination of the catalyst in the form of bulk ZnO (ZnO bulkform)has been done. The results showed that the optimum exposure time in the photoreduction process of Cr (VI)catalyzed by ZnO-Z is 25 hours and the optimum initial concentration of Cr (VI) is 25 mg/L. Photoreductionyield of Cr (VI) by catalyst ZnO-Z is higher than the ZnO bulkform.